2016
DOI: 10.1007/s00406-016-0684-7
|View full text |Cite
|
Sign up to set email alerts
|

The relevance of ‘mixed anxiety and depression’ as a diagnostic category in clinical practice

Abstract: According to ICD-10 criteria, mixed anxiety and depressive disorder (MADD) is characterized by co-occurring, subsyndromal symptoms of anxiety and depression, severe enough to justify a psychiatric diagnosis, but neither of which are clearly predominant. MADD appears to be very common, particularly in primary care, although prevalence estimates vary, often depending on the diagnostic criteria applied. It has been associated with similarly pronounced distress, impairment of daily living skills, and reduced healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
72
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 100 publications
(83 citation statements)
references
References 79 publications
4
72
0
7
Order By: Relevance
“…Thus, Beekman et al () estimated that 47–50% of older depressed individuals had a comorbid anxiety disorder. Several review papers suggest that mixed anxiety‐depression is the typical presentation in the elderly (Möller et al, ). However, because both are comorbid across the life‐cycle, the utility of including a mixed anxiety‐depression disorder specifically for older groups remains ambiguous, and more evaluation is required to establish a mixed anxiety‐depression construct in older people before regarding it as a distinctive presentation.…”
Section: Psychiatric Comorbidity Of Anxiety and Depressionmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, Beekman et al () estimated that 47–50% of older depressed individuals had a comorbid anxiety disorder. Several review papers suggest that mixed anxiety‐depression is the typical presentation in the elderly (Möller et al, ). However, because both are comorbid across the life‐cycle, the utility of including a mixed anxiety‐depression disorder specifically for older groups remains ambiguous, and more evaluation is required to establish a mixed anxiety‐depression construct in older people before regarding it as a distinctive presentation.…”
Section: Psychiatric Comorbidity Of Anxiety and Depressionmentioning
confidence: 99%
“…Moreover, its efficacy as a diagnostic class remains under dispute (Möller et al, )—it was not incorporated into the recently released DSM‐5 because the suggested diagnostic criteria were evaluated and classed as not adequately reliable. Experts have contested the interpretation of MADD based on conflicting results concerning both its diagnostic stability over time, and nosological inconsistencies between subthreshold and threshold presentations of anxiety and depressive disturbances (Möller et al, ).…”
Section: Diagnostic Relevance: Dsm‐v Contextmentioning
confidence: 99%
See 2 more Smart Citations
“…Its derivation is also obscure, and it serves only to further confuse matters diagnostically. As Möller et al () point out, the criteria are closely related to the anxious symptom scale proposed by Goldberg, Prisciandaro, and Williams () for the primary health care version of ICD‐11. For comparison, the DSM‐5 criteria are shown alongside the ICD‐11 proposal in Table .…”
Section: Mixed Anxiety and Depressive Disorder‐diagnostic Guidelines mentioning
confidence: 99%